Answer:
237
Step-by-step explanation:
multiply the length value by 10
<h3><u>Solution</u><u>:</u></h3>
Please find the photograph for the square root of 3.
- Firstly, you have to write 3 as 3. 00 00 00.
- Then we should find out the root of the perfect square which is less than 3. Here, 1 is the required perfect square root because 1 × 1 = 1 only which is less than 3.
- Now 3 - 1 = 2 and we are placing 2 zeros after it so that it will be 200. Now we have to add 1 with the divisor 1 which will be 2. Then we have to select a number to be placed beside this 2 in such a way that if we multiply this combined number with the new number, then we will get a number which is less than 200. We see that if we place 7 after 2 and multiply 27 with 7, we get 189 which is less than 200.
- Now 200 - 189 = 11 and we are placing 2 zeros after it so that it will be 1100. Now we have to add 7 with the divisor 27 which will be 34. Then we have to select a number to be placed beside this 34 in such a way that if we multiply this combined number with the new number, then we will get a number which is less than 1100. We see that if we place 3 after 34 and multiply 3 with 343, we get 1029 which is less than 1100.
- Now 1100 - 1029 = 71 and we are placing 2 zeros after it so that it will be 7100. Now we have to add 3 with the divisor 343 which will be 346. Then we have to select a number to be placed beside this 346 in such a way that if we multiply this combined number with the new number, then we will get a number which is less than 7100. We see that if we place 2 after 346 and multiply 2 with 3462, we get 6924 which is less than 7100.
- So, we will get the quotient as 1.732 (corrected to three places of decimal).
4√3
= 4 × 1.732
= 6.928
<h3><u>Answer:</u></h3>
<u>6</u><u>.</u><u>9</u><u>2</u><u>8</u>
Hope it helps
SOLUTIONS
Solve a given equations or algebraic symbols?
![\begin{gathered} f(x)=x^2+2x \\ g(x)=1-x^2 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20f%28x%29%3Dx%5E2%2B2x%20%5C%5C%20g%28x%29%3D1-x%5E2%20%5Cend%7Bgathered%7D)
(A)
![\begin{gathered} (f+g)(x)=(x^2+2x)+(1-x^2) \\ collect\text{ like terms} \\ x^2-x^2+2x+1 \\ (f+g)(x^)=2x+1 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20%28f%2Bg%29%28x%29%3D%28x%5E2%2B2x%29%2B%281-x%5E2%29%20%5C%5C%20collect%5Ctext%7B%20like%20terms%7D%20%5C%5C%20x%5E2-x%5E2%2B2x%2B1%20%5C%5C%20%28f%2Bg%29%28x%5E%29%3D2x%2B1%20%5Cend%7Bgathered%7D)
(B)
![\begin{gathered} (f-g)(x)=(x^2+2x)-(1-x^2) \\ =x^2+2x-1+x^2 \\ =x^2+x^2+2x-1 \\ (f-g)(x)=2x^2+2x-1 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20%28f-g%29%28x%29%3D%28x%5E2%2B2x%29-%281-x%5E2%29%20%5C%5C%20%3Dx%5E2%2B2x-1%2Bx%5E2%20%5C%5C%20%3Dx%5E2%2Bx%5E2%2B2x-1%20%5C%5C%20%28f-g%29%28x%29%3D2x%5E2%2B2x-1%20%5Cend%7Bgathered%7D)
(C)
![\begin{gathered} fg(x)=(x^2+2x)(1-x^2) \\ =x^2-x^4+2x-2x^3 \\ fg(x)=-x^4-2x^3+x^2+2x \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20fg%28x%29%3D%28x%5E2%2B2x%29%281-x%5E2%29%20%5C%5C%20%3Dx%5E2-x%5E4%2B2x-2x%5E3%20%5C%5C%20fg%28x%29%3D-x%5E4-2x%5E3%2Bx%5E2%2B2x%20%5Cend%7Bgathered%7D)
(D)
0.8888888 = 8/9
2.8888888 = 26/9
-2.888888 = -26/9
Answer:
y = - 3x + 21
Step-by-step explanation:
The equation of a line in slope- intercept form is
y = mx + c ( m is the slope and c the y- intercept )
y = - 3x + 4 ← is in slope- intercept form
with slope m = - 3
Parallel lines have equal slopes , then
y = - 3x + c ← is the partial equation
To find c substitute (7, 0 ) into the partial equation
0 = - 21 + c ⇒ c = 0 + 21 = 21
y = - 3x + 21 ← equation of parallel line